An Analysis of Selected Characteristics in Metaphysical Poetry - Azam, Yasir (European Publisher, 2019)
Metaphysical poetry generally refers to the works of a relatively small group of seventeenth century English poets. They are uniquely different in comparison to other types of poetry as they were written in a specific style, peculiar to the nature of metaphysics. Although there are different kinds of characteristics defining the essence of metaphysical poetry, this study focuses on four prominent ones namely; intellectuality, imageries and conceits, expression of ideas and feelings, and the development of logical arguments. This study explores the selected characteristics in terms of how they are connected with each other in two metaphysical poems, John Donne’s The Good-Morrow and Andrew Marvell’s The Definition of Love. From the discussion, it is evident that all four characteristics under study are served throughout the two poems. The analysis shows that the poets use their intellectual abilities to construct elaborated metaphysical imageries and conceits, which they then use as a platform to convey their ideas and feelings. The ideas and feeling are reasoned through logical arguments, which requires high degree of intellectual abilities not only to construct but also to comprehend them. Such connection between the characteristics serve to support the essence and uniqueness of what is known as metaphysical poetry.